Analisis Pemikiran Hukum Islam tentang Sistem Penghimpunan dan Penyaluran Dana pada Lembaga Keuangan Syariah (LKS) dan Institusi Keuangan Non-Bank (IKNB) - Rara Rita Erawati, dkk, Raden (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2026)
System Islamic finance in Indonesia has developed fast, but still faces challenges in maintaining balance between economic growth and depth of sharia compliance. This article analyzes thinking related to Islamic law system collection and distribution of funds in Islamic Financial Institutions (LKS) and Islamic Institutions Non-Bank Finance (IKNB), with prioritization of contract integrity, implementation of maqashid sharia, as well as continuity mark Islamic economics in practice modern finance. Through a normative-comparative approach and critical analysis against the DSN-MUI fatwa, OJK regulations, and contemporary jurisprudence literature, this research reveals the existence of domination contracts debt-based such as murabahah and ijarah, which have the potential to shift the essence of Islamic finance from principle for results ( mudarabah and musyarakah ) towards a similar conventional transactional model. In addition, micro institutions such as BMT and Islamic fintech are experiencing dilemmas in implementing sharia governance , especially related to Sharia Supervisory Board readiness and discipline dual-track accounting . This study also highlights potential big integration of social instruments such as zakat, infaq , and digital waqf as drivers of micro economic stability, provided that supported by synergistic regulations and adequate sharia literacy. With ​Thus , this research recommends the need for harmonization of inter-authority regulations, strengthening sharia governance, and innovation based value - based banking to realize an Islamic finance system that is not only competitive, but also transformative. Keywords: Islamic law, sharia finance, fund raising, fund distribution, sharia fintech